Awareness of Open Data among Researchers in Selected Public Universities in Tanzania - Muneja, Paul; Buhomoli, Obadia Shadrack (University of Dar es Salaam Library Journal, 2021)
This study explored the extent of researchers ' awareness on open data (OD) in selected universities in Tanzania. Various scholars have highlighted several benefits that are associated with the adoption and use of Open Data that include validation and accountability of research findings, minimization of duplication of studies, protection of research integrity and increased visibility of both research results as well as the host institution. The study employed a cross-section research design which combined qualitative and quantitative approaches. A sample of 200 researchers was drawn from a sampling frame of 1846 using both probability and non-probability sampling techniques. The findings of this study have revealed that majority of respondents lacked a deep understanding of OD concept. Based on the findings, the study recommends that open data weeks and open data days should be adopted and used by academic and research institutions to create awareness on OD. Academic institutions need to integrate OD and research data management in course of their degree programmes, especially at postgraduate level. Awareness creation mechanisms such as workshops should regularly be used to create OD awareness at all levels of academic institutions.